Status and perspective of lab-on-a-chip systems for common diseases: a systematic review from 2003 to 2013. (January 2016) - Gebauer, Alexander; Schmidt, Silke; Hoffmann, Wolfgang
Background: Lab-on-a-chip systems (LOCs) are a useful aid for the individualization of therapeutic algorithms at the point-of-care.Materials & methods: We performed a systematic literature review on LOCs for diseases with a global impact for healthcare.Results: A total of 1007 articles matched the previously specified search criteria, thereof 65 studies could be included in this review. A total of 55 different LOCs were evaluated, most for diagnosis or monitoring of cancer (n = 24). For other diseases we found considerably less analyzed LOCs. The analytical performance of the LOCs was usually very good, 37 (67%) LOCs had a sensitivity higher than 90%.Conclusion: Although LOC systems performance has been positively evaluated in the great majority of studies, the testing was mostly limited to the research laboratory setting rather than real-world scenarios.